Maternal inflammation leads to impaired glutamate homeostasis and up-regulation of Glutamate Carboxypeptidase II in activated microglia in the fetal/newborn rabbit brain - Zhang, Zhi (Neurobiol Dis, 2016)
Astrocyte dysfunction and excessive activation of glutamatergic systems has been implicated in a number of neurologic disorders, including periventricular leukomalacia (PVL) and cerebral palsy (CP). However, the role of chorioamnionitis on glutamate homeostasis in the fetal and neonatal brains is not clearly understood. We have previously shown that intrauterine endotoxin administration results in intense microglial ‘activation’ and increased pro-inflammatory cytokines in the periventricular region (PVR) of the neonatal rabbit brain. In this study, we assessed the effect of maternal inflammation on key components of the glutamate pathway and its relationship to astrocyte and microglial activation in the fetal and neonatal New Zealand white rabbit brain. We found that intrauterine endotoxin exposure at gestational day 28 (G28) induced acute and prolonged glutamate elevation in the PVR of fetal (G29, 1 day post-injury) and postnatal day 1 (PND1, 3 days post-injury) brains along with prominent morphological changes in the astrocytes (soma hypertrophy and retracted processes) in the white matter tracts. There was a significant increase in glutaminase and N-Methyl-D-Aspartate receptor (NMDAR) NR2 subunits expression along with decreased glial L-glutamate transporter 1 (GLT1) in the PVR at G29, that would promote acute dysregulation of glutamate homeostasis. This was accompanied with significantly decreased TGF-β1 at PND1 in CP kits indicating ongoing neuroinflammation. We also show for the first time that glutamate carboxypeptidase II (GCPII) was significantly increased in the activated microglia at the periventricular white matter area in both G29 and PND1 CP kits. This was confirmed by in vitro studies demonstrating that LPS activated primary microglia markedly upregulate GCPII enzymatic activity. These results suggest that maternal intrauterine endotoxin exposure results in early onset and long-lasting dysregulation of glutamate homeostasis, which may be mediated by impaired astrocyte function and GCPII upregulation in activated microglia.